Four‐day plaque regrowth evaluation of a peptide chewing gum in a double‐blind randomized clinical trial - Brian Kirkwood; Michael Miller; Jeffery Milleman; Kimberly Milleman; Kai Leung (Wiley, 2020)
Abstract Objective Antimicrobial peptide, KSL‐W, formulated as an antiplaque chewing gum (APCG), was tested to evaluate the dental plaque inhibition activity and safety in an IRB approved and FDA regulated 4‐day plaque regrowth clinical study. Methods This Phase 2 two‐armed placebo‐controlled, double blind, randomized (1:1), multiple dose, and single‐center study was evaluated in a proof of concept for the APCG containing 30 mg antimicrobial peptide KSL‐W. Twenty six generally healthy subjects were consented and randomized into the study. The subjects were administered a dose three times per day for four treatment days following a complete dental prophylaxis. Participants were prohibited from conducting oral hygiene care (teeth brushing, flossing, and/or mouth wash rinse) for the duration of the trial. Twelve to 16 hr prior to the baseline visit, the subjects were to abstain from oral hygiene care. The Quigley-Hein Turesky plaque index (QHT) score and the oral soft tissue clinical exams were obtained at both Day 0 and Day 4. Results All randomized study subjects that received either APCG or placebo gum completed the study with no significant adverse events recorded. The APCG significantly inhibited the regrowth of dental plaque over the course of 4 days. The whole mouth data demonstrated a difference in the QHT between the APCG and the placebo gum of 1.14 (SE = 0.27) and 95% confidence bounds of 0.58, 1.70 with a two‐tailed P value of .0003. Conclusion Considering the limited sample size, the proof of concept analysis in this Phase 2 study confirmed that APCG is effective against dental plaque formation and safe for human use. (ClinicalTrials.gov Study ID# NCT02864901).